Public international law - Kaczorowska-Ireland, Alina (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The 6th edition of Public International Law continues the book's accessible, student-friendly tradition with a writing style that is both conversational and easy to read. Uniquely both a textbook and a casebook, the facts of each case and the details of decisions are succinctly set out, followed by detailed commentary and, where appropriate, a brief explanation of subsequent events. Fully up to date with all recent developments, the 6th edition covers the major areas of public international law and examines the leading cases of the ICJ and other international courts and tribunals, whilst paying attention to judgments of national courts, including the UK Supreme Court, the US Supreme Court, and courts of many other countries when they make challenging or novel contributions to international law. Features designed to support learning include highlighted key cases, introductory chapter overviews and concise outlines, and recommended further reading. New to this edition are study boxes which apply public international law to recent events and examine controversial legal issues in a constructive way, including the ongoing armed conflict between Russia and Ukraine, the murder of Jamal Khashoggi and the judicial battle of Julian Assange. Diagrammatic aides-mémoires at the end of each chapter have also been updated to further summarise topics covered in that chapter. This book is an ideal learning tool for students of law or political science, practitioners, legal advisors and provides a clear and straight-forward overview for anyone with an interest in international law"--
History and nature of international law -- Sources of international law -- The law of treaties -- International law and municipal law -- International personality -- Recognition of states, governments and intergovernmental organisations in international law -- Territorial sovereignty -- The law of the sea -- Jurisdiction -- Immunity from national jurisdiction -- State responsibility for wrongful acts -- An overview of the international protection of human rights -- Self-determination of peoples -- Peaceful settlement of disputes between states -- The use of force -- Collective security -- International humanitarian law (IHL).
BIBINDX
Keywords: International law